Preparation method and application of integrated self-powered sensing fabric
By using a braided structure of negative friction yarn and positive friction layer in the wearable sweat sensor, an integrated self-powered sensing fabric is formed, which solves the problems of low output power density and poor compatibility in the prior art, and realizes an efficient, sensitive and degradable sweat sensing function.
Patent Information
- Application Number
- CN202510196232.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing wearable sweat sensors have problems such as low output power density, poor compatibility with sensing elements and poor breathability, which limits their applications in integration and miniaturization.
The negative friction yarn is used, consisting of a conductive inner core and a negatively charged polymer nanofiber layer, and is prepared by electrospinning process. It combines a braided structure of a positive friction layer and a negative friction layer to form an integrated self-powered sensing fabric.
It achieves high output power density, high sensitivity, good breathability and degradability, and can perform sweat glucose detection in a short charging time, which is suitable for non-invasive health monitoring and early disease detection.
Smart Images

Figure CN119843405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fabrics, and in particular to a preparation method and application of an integrated self-powered sensing fabric. Background Art
[0002] Wearable sweat sensors have attracted widespread attention due to their potential in non-invasive health monitoring. However, most human motion energy harvesters used for wearable sweat sensors have problems such as low output power density, poor compatibility with sensor elements, and poor air permeability, which poses a huge challenge to continuous sweat sensing. For example, a Chinese patent with publication number CN109239152B discloses a method for preparing an electrochemical sensing fabric woven from sensing fibers. The fabric uses lithium-ion batteries as a power source. Traditional power sources such as batteries have the disadvantages of requiring repeated charging, being non-deformable or degradable. At the same time, existing wearable electronic devices for sweat sensing are assembled from two independent components: a power supply component and a sensor component for performing monitoring functions, which limits the application of wearable electronic devices in terms of integration and miniaturization.
[0003] Therefore, there is an urgent need to develop an integrated self-powered electrochemical sensing fabric with high output power density, high sensitivity, high breathability and degradability for real-time non-invasive monitoring of daily human health status and early disease detection and management. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of an integrated self-powered sensing fabric, which, in the field of wearable sweat sensors, converts mechanical energy generated by motion into electrical energy in low-frequency motion scenarios, and can achieve sweat glucose detection in a shorter charging time.
[0005] In one aspect of the present invention, the present invention provides a negative friction yarn. According to an embodiment of the present invention, the negative friction yarn comprises a conductive inner core and a negatively charged polymer nanofiber layer from inside to outside, and the negatively charged polymer is a modified thermoplastic polyurethane (TPUs) based on polycaprolactone (PCL).
[0006] In another aspect of the present invention, the present invention provides a method for preparing a negative friction yarn. According to an embodiment of the present invention, the method comprises the following steps:
[0007] (1) Negatively charged modified thermoplastic polyurethane was prepared by step-by-step polymerization, named negatively charged PCLU-HFDD@WCNTs nanofiber layer;
[0008] (2) Through the electrospinning process, a negatively charged PCLU-HFDD@WCNTs nanofiber layer is coated on the outside of the conductive inner core to form a negative friction yarn.
[0009] In addition, the method for preparing the negative friction yarn according to the above embodiment of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, in step (1), the raw materials in the step-by-step polymerization reaction include diols, polyisocyanates, chain extenders, catalysts, and organic solvents; in step (2), the electrospinning process uses a fluoropolyurethane (PCLU-HFDD) spinning solution, and the concentration of the PCLU-HFDD spinning solution is 15wt% to 19wt%.
[0011] In some embodiments of the present invention, in the step-by-step polymerization reaction, the diol is polycaprolactone-diol, the polyisocyanate is dicyclohexylmethylmethane-4, the chain extender is a fluorine-containing chain extender, the catalyst is dibutyltin dilaurate, and the organic solvent is one of tetrahydrofuran, ethyl acetate, and acetone. The above raw materials are mixed with 18wt% to 22wt% of carbon nanotubes (WCNTs) by mass fraction, and the reaction is carried out at 50-55°C for 6-7 hours.
[0012] In another aspect of the present invention, the present invention provides an integrated self-powered sensing fabric. According to an embodiment of the present invention, it includes:
[0013] The positive friction layer is woven from a sensing yarn and a positive friction yarn. The sensing yarn includes a glucose sensing inner core, a hydrophilic positively charged polymer nanofiber layer and a hydrophobic positively charged polymer nanofiber layer from the inside to the outside. The positive friction yarn includes a conductive inner core and a positively charged polymer nanofiber layer from the inside to the outside.
[0014] A negative friction layer is woven from the negative friction yarn.
[0015] In addition, the integrated self-powered sensing fabric according to the above embodiment of the present invention may also have the following additional technical features:
[0016] In some embodiments of the present invention, the average pore size of the hydrophilic positively charged polymer nanofiber layer is smaller than the average pore size of the hydrophobic positively charged polymer nanofiber layer.
[0017] In some embodiments of the present invention, the glucose sensor core is a conductive core deposited with a glucose sensor material, preferably a metal oxide glucose sensor material or an enzyme-based glucose sensor material, more preferably a metal oxide glucose sensor material; the conductive core can be a conventional conductive material in the art, preferably carbon fiber (CF), more preferably, the conductive core is composed of a plurality of bundles of carbon fibers. The conductive core composed of a plurality of bundles of carbon fibers has a higher specific surface area, which is conducive to the deposition of the sensing material and improves the sensing sensitivity.
[0018] and / or, the polymers in the hydrophilic positively charged polymer nanofiber layer and the hydrophobic positively charged polymer nanofiber layer are flexible polymers of positive polarity in the triboelectric series;
[0019] And / or, the polymer in the negatively charged polymer nanofiber layer is a flexible polymer with negative polarity in the triboelectric series and a modified polymer thereof;
[0020] In some embodiments of the present invention, the glucose sensor core is composed of a plurality of bundles of carbon fibers deposited with Cu2O, and the method of applying Cu2O to the conductive core is to use a Cu-containing electrolyte for electrodeposition. The preparation method of the Cu-containing electrolyte may include: mixing a CuSO4·5H2O aqueous solution and a lactic acid solution, and then adding a NaOH aqueous solution to adjust the pH value to 10-11. The molar concentration ratio of the CuSO4·5H2O and the lactic acid is (1-5):10, for example, 3:10. The conditions for the electrodeposition preferably include: a current density of 2-3 mA cm -2 The deposition time is 10 to 20 minutes, for example, 15 minutes. Since enzyme-based glucose sensing materials have high fixed costs, low sensitivity, and low stability, Cu2O as a glucose sensing material has low cost, high sensitivity, selectivity, and long-term stability, which is superior to glucose oxidase.
[0021] And / or, the polymers in the hydrophilic positively charged polymer nanofiber layer and the hydrophobic positively charged polymer nanofiber layer are polylactic acid-glycolic acid copolymer; and / or, the polymer in the negatively charged polymer nanofiber layer is a flexible polymer with negative polarity in the triboelectric sequence, which is polydimethylsiloxane.
[0022] In another aspect of the present invention, the present invention provides a method for preparing an integrated self-powered sensing fabric. According to an embodiment of the present invention, the method comprises the following steps:
[0023] S1. A positively charged polymer nanofiber layer is coated on the outside of the glucose sensor core by an electrospinning process, and a hydrophilic treatment is performed to form a hydrophilic positively charged polymer nanofiber layer, and then a hydrophobic positively charged polymer nanofiber layer is coated to form a sensing yarn; the hydrophilic treatment is a conventional hydrophilic treatment method in the art, such as oxygen plasma treatment, and the time of the oxygen plasma treatment is preferably 5 to 10 minutes, for example, 5 minutes.
[0024] S2, coating a hydrophobic positively charged polymer nanofiber layer on the outside of the conductive inner core through an electrospinning process to form a positive friction yarn, and weaving the positive friction yarn and the sensing yarn in one layer to form a positive friction layer;
[0025] S3, weaving the negative friction yarns together to form a negative friction layer;
[0026] S4. Weaving and assembling the positive friction layer, the negative friction layer, the reference electrode yarn, and the counter electrode yarn together to obtain the integrated self-powered sensing fabric.
[0027] In addition, the method for preparing the integrated self-powered sensor fabric according to the above embodiment of the present invention may also have the following additional technical features:
[0028] In some embodiments of the present invention, the electrospinning process uses a polylactic acid-co-glycolic acid spinning solution, the concentration of the polylactic acid-co-glycolic acid spinning solution of the hydrophilic positively charged polymer nanofiber layer is 13wt% to 17wt%, and the concentration of the polylactic acid-co-glycolic acid spinning solution of the hydrophobic positively charged polymer nanofiber layer is 18wt% to 22wt%; in step S2, the electrospinning process uses a polylactic acid-co-glycolic acid spinning solution, and the concentration of the polylactic acid-co-glycolic acid spinning solution is 18wt% to 22wt%. Wherein, wt% represents the mass percentage of PLGA in the PLGA spinning solution.
[0029] The PLGA spinning solution is prepared by dissolving PLGA in a solvent. The solvent may be one or more of tetrahydrofuran, N,N-dimethylformamide, dichloroethane, ethyl acetate, acetone and chlorobenzene, such as a mixed solvent of tetrahydrofuran and N,N-dimethylformamide. When the solvent is a mixed solvent of tetrahydrofuran and N,N-dimethylformamide, preferably, the volume ratio of tetrahydrofuran to N,N-dimethylformamide is (6-9):3, such as 7:3.
[0030] The electrospinning process of the hydrophilic positively charged polymer nanofiber layer satisfies one or more of the following conditions (a)-(d):
[0031] (a) the spinning voltage is 14-16 kV, for example 15 kV;
[0032] (b) the spinning humidity is 45% rh to 55% rh, for example 50% rh;
[0033] (c) the spinning temperature is 25 to 31° C., for example 25° C.;
[0034] (d) The spinning time is 10 to 12 hours, for example 10 hours.
[0035] In the above embodiment, the electrospinning process of the hydrophobic positively charged polymer nanofiber layer satisfies one or more of the following conditions (a)-(d):
[0036] (a) the spinning voltage is 7 to 9 kV, for example 8 kV;
[0037] (b) the spinning humidity is 45% rh to 55% rh, for example 50% rh;
[0038] (c) the spinning temperature is 25 to 31° C., for example 25° C.;
[0039] (d) The spinning time is 10 to 12 hours, for example 10 hours.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The present invention utilizes the high electronegativity of fluorine element and introduces a fluorine-containing chain extender during the polymerization process of thermoplastic polyurethane. The average surface potential of the prepared PCLU-HFDD yarn is as high as -68.5 mV, which is 2 times higher than that of the unmodified yarn.
[0042] (2) The open circuit voltage, short circuit current, and short circuit charge generated by the TENG prepared by the rotational collection method of the present invention are much higher than those of the TENG prepared by the parallel collection method, and it has a higher output power (1.06 mW) and can be monitored with an average charging time of only 21 seconds.
[0043] (3) The integrated self-powered sensing fabric prepared by the present invention has a higher sensitivity (38.25 mA·cm -2 ·mM) and excellent reproducibility, which is effective in practical applications.
[0044] (4) The integrated self-powered sensing fabric prepared by the present invention can still maintain a high sweat collection efficiency after multiple washing and drying steps, and the output voltage of the sensing fabric remains stable in multiple washing cycle tests, and the retention rate is close to 95%.
[0045] (5) The integrated self-powered sensing fabric prepared by the present invention is mainly composed of biodegradable materials, and the outer shells of all yarns show excellent biodegradability, which can achieve outer shell degradation and CFs recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a schematic diagram of the structure of the integrated self-powered fabric prepared in Example 3 of the present invention, in which: 1, sensing yarn, 2, counter electrode yarn, 3, reference electrode yarn, 4, negative friction layer, 5, positive friction layer;
[0047] Figure 2 is a SEM image of the negative friction yarn in Example 1 of the present invention;
[0048] Figure 3 This is a SEM image of the negative friction yarn in Comparative Example 1 of the present invention;
[0049] Figure 4The output voltage of the integrated self-powered sensing fabric prepared in Example 3 of the present invention and Comparative Example 2 under the same test conditions;
[0050] Figure 5 The output current of the integrated self-powered sensing fabric prepared in Example 3 of the present invention and Comparative Example 2 under the same test conditions;
[0051] Figure 6 This is a graph showing changes in glucose concentration over time during the detection process of Example 3 of the present invention;
[0052] Figure 7 This is an infrared schematic diagram of Example 3 of the present invention after heating;
[0053] Figure 8 This is a distribution diagram of charging time in Example 3 of the present invention;
[0054] Fig. 9 A comparison chart of sweat glucose concentration data non-invasively monitored using the integrated self-powered fabric of Example 3 of the present invention and blood glucose levels detected invasively;
[0055] Fig.10 These are photographs showing the degradation of the positive friction yarn and the negative friction yarn in Application Example 1 of the present invention in a sodium hydroxide solution (pH=14). DETAILED DESCRIPTION
[0056] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] Carbon fiber bundles (TZ700S, 12K) were purchased from Weihai Guangwei Composite Materials Co., Ltd., and polylactic acid-co-glycolic acid (PLGA, MW=80000), polycaprolactone diol (PCL-diol, Mn=2000), dicyclohexylmethylmethane-4 (HMDI), dibutyltin dilaurate (DBTDL), hexafluorodecanediol (HFDD), N,N-dimethylformamide (DMF), tetrahydrofuran (THF), sodium hydroxide (NaOH), cupric sulfate pentahydrate (CuSO4.5H2O), phosphate buffered saline (PBS), uric acid, urea, tryptophan, tyrosine, sodium chloride (NaCl), ammonium chloride (NH4Cl), ascorbic acid, glucose, DL-lactic acid, polyvinyl butyral (PVB) and ethylene oxide block copolymer (Pluronic F-127) were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0058] Ag / AgCl slurry was purchased from Shanghai Julong Electronic Technology Co., Ltd., and multi-walled carbon nanotubes (MWCNT, 8-15 nm, >95%) were provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.
[0059] Example 1
[0060] A PCLU-HFDD@WCNTs negative friction yarn, the preparation method of which comprises the following steps:
[0061] (1) Synthesis of PCLU-HFDD@WCNTs: The raw materials are 5 g of PCL-diol, 2.22 g of dicyclohexylmethylmethane-4 (HMDI), 2.31 g of fluorinated chain extender (HFDD), 20 μL of dibutyltin dilaurate (DBTDL), and 30 mL of tetrahydrofuran (THF) as the organic solvent. Finally, they are mixed with 20 wt% of WCNTs.
[0062] (2) preparing a solution obtained by mixing tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 7:3 to obtain a spinning solution of PCLU-HFDD@WCNTs 20 wt%;
[0063] (3) CFs (carbon fibers) were fixed on the rotating collector of the electrospinning machine, and 20 wt % spinning solution was used for spinning at 8 kV, 50% rh, and 25 ° C for 10 h to obtain PCLU-HFDD@WCNTs negative friction yarn.
[0064] Example 2
[0065] The method for preparing the positive friction layer comprises the following steps:
[0066] (1) Preparation of Janus sensing yarn
[0067] Mix 0.3 mol / L CuSO4·5H2O and 1 mol / L lactic acid solution in an electrolytic cell, then add 5 mol / L NaOH aqueous solution to adjust the pH value of the electrolyte to 11 and maintain the current density at 2 mA·cm -2, placing CF, and drying the Cu2O-CF after deposition for 15 minutes; preparing two solutions obtained by mixing tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 7:3, dissolving appropriate amounts of PLGA therein respectively to obtain a 13wt% spinning solution; fixing the Cu2O-CF on a rotating collector of an electrospinning machine, first using a 13wt% spinning solution, spinning for 10 hours at 15kv, 50%rh, and 25°C, removing it and treating it with oxygen plasma for 5 minutes, and coating the outside of the Cu2O-CF with a hydrophilic PLGA nanofiber layer; fixing the obtained product on an electrospinning machine, and then using a 13wt% spinning solution, spinning for 2 hours at a voltage of 15kv, 50%rh, and 25°C, and coating the outside with a hydrophobic PLGA nanofiber layer to obtain a sensing yarn.
[0068] (2) Preparation of positive friction yarn
[0069] The CF was fixed on the rotating collector of the electrospinning machine, and 20 wt % PLGA spinning solution was first used to spin at a voltage of 8 kV for 10 h to obtain positive friction yarn.
[0070] (3) The positive friction electric yarn and the sensing yarn are woven together to form a positive friction layer.
[0071] The negative friction yarn prepared in Example 1 and the positive friction yarn prepared in Example 2 were placed in a sodium hydroxide solution (pH=14) for degradation. The results are as follows: Fig.10 As shown, the polymer shells of both positive and negative friction yarns were damaged after 2 hours, and the CF could be recycled and reused.
[0072] Example 3
[0073] The integrated self-powered sensing fabric, the preparation method thereof comprises the following steps:
[0074] (1) Preparation of Janus reference electrode yarn
[0075] Ag / AgCl slurry was coated on CF (carbon fiber), put into a 60°C oven, and dried to obtain Ag / AgCl-CF; Ag / AgCl-CF was fixed on a rotating collector of an electrospinning machine, first 15wt% spinning solution was used, spinning was carried out at a voltage of 15kv for 10h, after removal, oxygen plasma treatment was performed for 5min, and then 20wt% spinning solution was used, spinning was carried out at a voltage of 8kv for 2h to obtain Janus reference electrode yarn.
[0076] (2) Preparation of Janus electrode yarn
[0077] The CF was fixed on the rotating collector of the electrospinning machine, and 15 wt% spinning solution was used to spin at a voltage of 15 kV for 10 h. After being removed, it was treated with oxygen plasma for 5 min, and then 20 wt% spinning solution was used to spin at a voltage of 8 kV for 2 h to obtain Janus counter electrode yarn.
[0078] (3) Preparation of integrated self-powered sensing fabrics
[0079] The negative friction electric yarns obtained in Example 1 are woven together to form a negative friction layer 4, and then the reference electrode yarn 3, the counter electrode yarn 2 and the positive friction layer 5 prepared in Example 2 (the positive friction electric yarn and the sensor yarn 1 are woven together in one layer) are woven together, and then the negative friction layer 4 and the positive friction layer 5 are sewn together around the periphery by an embroidery process to obtain an electrochemical fabric, whose structure is as follows: Figure 1 shown.
[0080] like Figure 8 As shown, the integrated self-powered sensing fabric has a higher output power (1.06mW) and can be monitored with an average charging time of only 21 seconds.
[0081] Comparative Example 1
[0082] This comparative example provides a PCLU-HFDD@WCNTs negative friction sensing yarn, and the preparation method thereof comprises the following steps:
[0083] (1) preparing a solution obtained by mixing tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 7:3, and dissolving the PCLU-HFDD@WCNTs prepared in Example 1 therein to obtain a 20 wt % spinning solution;
[0084] (2) Using 20 wt% spinning solution, spinning for 10 h at 8 kV, 50% rh, and 25 °C, the fibers were collected on a flat collector. The fibers were then wrapped on CFs to obtain a flat collector negative friction layer sensing yarn.
[0085] The performance of the negative triboelectric yarn in Example 1 and Comparative Example 1 was tested by using Keithley 2400 triboelectric nanogenerator test system. The obtained SEM images are shown in Figure 2 and 3 As shown, the surface roughness of the yarn in Example 1 is rougher than that in Comparative Example 1.
[0086] Comparative Example 2
[0087] The integrated self-powered sensing fabric is different from Example 3 in that the negative friction yarn is obtained by the method of Comparative Example 1, and the other steps are the same as those of Application Example 1.
[0088] The integrated self-powered sensing fabrics obtained in Example 3 and Comparative Example 2 were subjected to the following performance tests:
[0089] 1. Take the integrated self-powered sensor fabrics obtained in Example 3 and Comparative Example 2, and use the friction nanogenerator test system to test the output performance. Figure 4 and 5 As shown, the open circuit voltage (Voc) and short circuit current (Isc) generated by the application example 1 based on the rotating current collecting yarn at a frequency of 5 Hz reached 117.08 V and 9.85 μA, respectively. In contrast, under the same test conditions, the Voc and Isc of the comparative example 2 based on the parallel collecting yarn were only 25.41 V and 1.04 μA, respectively.
[0090] 2. Take the integrated self-powered sensing fabric obtained in Example 3, use wires to connect the three electrodes to a portable electrochemical workstation, use PBS solution to simulate the human sweat environment, continuously add glucose solutions of different concentrations, collect current and fit the relationship curve between concentration and current as shown in the figure. Figure 6 As shown (each concentration was tested 5 times), in the range of 3 to 120 μM glucose concentration, the sensitivity of the electrochemical fabric was 3824.88 mA cm -2 mM -1 , proving that the integrated self-powered sensing fabric prepared in Example 3 has higher sensitivity.
[0091] 3. The positive friction layer prepared in Example 1 was heated to 2.00 V at a working voltage of 0.0075 W / cm 2 Heating is performed under low power density. The infrared image after heating is as follows: Figure 7 As shown, the super-hydrophobic heating electrode substrate prepared in Example 1 was heated at a working voltage of 2.00 V and a temperature of 0.0075 W / cm 2 At low power density, the temperature can reach 50.1°C, which is much higher than the threshold of 42°C for thermal stimulation of skin sweating. Therefore, electric heating can stimulate skin sweating and improve sweat collection efficiency.
[0092] 4. Volunteers wore the integrated self-powered sensor fabric prepared in Example 3 and a commercially available portable blood glucose meter at the same time, and compared the non-invasively monitored sweat glucose concentration data with the invasively detected blood glucose level. The comparison results are as follows: Fig. 9 As shown, the trend of sweat glucose concentration monitored by the integrated sensing fabric is the same as the result of the portable blood glucose meter.
[0093] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A negative friction yarn, characterized in that: The negative friction yarn comprises a conductive inner core and a negatively charged polymer nanofiber layer from the inside to the outside, and the negatively charged polymer is a modified thermoplastic polyurethane based on polycaprolactone.
2. A method for preparing the negative friction yarn according to claim 1, characterized in that: The following steps are involved: (1) Negatively charged modified thermoplastic polyurethane was prepared by step-by-step polymerization, named negatively charged PCLU-HFDD@WCNTs nanofiber layer; (2) Through the electrospinning process, a negatively charged PCLU-HFDD@WCNTs nanofiber layer is coated on the outside of the conductive inner core to form a negative friction yarn.
3. The method for preparing negative friction yarn according to claim 2, characterized in that: In step (1), the raw materials in the stepwise polymerization reaction include diol, polyisocyanate, chain extender, catalyst, and organic solvent; In step (2), the electrospinning process uses a fluorine-containing polyurethane spinning solution, and the concentration of the PCLU-HFDD spinning solution is 15wt% to 19wt%.
4. The method for preparing negative friction yarn according to claim 3, characterized in that: In the step-by-step polymerization reaction, the diol is polycaprolactone-diol, the polyisocyanate is dicyclohexylmethylmethane-4, the chain extender is a fluorine-containing chain extender, the catalyst is dibutyltin dilaurate, and the organic solvent is one of tetrahydrofuran, ethyl acetate, and acetone. The above raw materials are mixed with carbon nanotubes with a mass fraction of 18wt% to 22wt%, and the reaction is carried out at 50-55°C for 6-7 hours.
5. Integrated self-powered sensing fabric, characterized in that, include: A positive friction layer, wherein the positive friction layer is woven from a sensing yarn and a positive friction yarn, wherein the sensing yarn comprises a glucose sensing inner core, a hydrophilic positively charged polymer nanofiber layer and a hydrophobic positively charged polymer nanofiber layer in sequence from the inside to the outside, and the positive friction yarn comprises a conductive inner core and a positively charged polymer nanofiber layer in sequence from the inside to the outside; A negative friction layer, wherein the negative friction layer is woven from the negative friction yarn according to claim 1.
6. The integrated self-powered sensing fabric according to claim 5, characterized in that: The average pore size of the hydrophilic positively charged polymer nanofiber layer is smaller than the average pore size of the hydrophobic positively charged polymer nanofiber layer.
7. The integrated self-powered sensing fabric according to claim 6, characterized in that: The glucose sensing inner core is a conductive inner core on which glucose sensing material is deposited; and / or, the polymers in the hydrophilic positively charged polymer nanofiber layer and the hydrophobic positively charged polymer nanofiber layer are flexible polymers of positive polarity in the triboelectric series; And / or, the polymer in the negatively charged polymer nanofiber layer is a flexible polymer with negative polarity in the triboelectric series and a modified polymer thereof.
8. The integrated self-powered sensing fabric according to claim 6, characterized in that: The glucose sensor inner core is composed of a plurality of bundles of carbon fibers deposited with Cu2O; and / or, the polymers in the hydrophilic positively charged polymer nanofiber layer and the hydrophobic positively charged polymer nanofiber layer are poly(lactic acid-glycolic acid) copolymers; And / or, the polymer in the negatively charged polymer nanofiber layer is a flexible polymer with negative polarity in the triboelectric series and is polydimethylsiloxane.
9. A method for preparing the integrated self-powered sensor fabric according to claim 5, characterized in that: The following steps are involved: S1. A positively charged polymer nanofiber layer is coated on the outside of the glucose sensor core by an electrospinning process, and a hydrophilic treatment is performed to form a hydrophilic positively charged polymer nanofiber layer, and then a hydrophobic positively charged polymer nanofiber layer is coated to form a sensing yarn; S2, coating a hydrophobic positively charged polymer nanofiber layer on the outside of the conductive inner core through an electrospinning process to form a positive friction yarn, and weaving the positive friction yarn and the sensing yarn in one layer to form a positive friction layer; S3, weaving the negative friction yarns together to form a negative friction layer; S4. Weaving and assembling the positive friction layer, the negative friction layer, the reference electrode yarn, and the counter electrode yarn together to obtain the integrated self-powered sensing fabric.
10. The method for preparing the integrated self-powered sensor fabric according to claim 9, characterized in that: In step S1, the electrospinning process uses a polylactic acid-glycolic acid copolymer spinning solution, the concentration of the polylactic acid-glycolic acid copolymer spinning solution of the hydrophilic positively charged polymer nanofiber layer is 13wt% to 17wt%, and the concentration of the polylactic acid-glycolic acid copolymer spinning solution of the hydrophobic positively charged polymer nanofiber layer is 18wt% to 22wt%; In step S2, the electrospinning process uses a polylactic acid-co-glycolic acid spinning solution, and the concentration of the polylactic acid-co-glycolic acid spinning solution is 18 wt% to 22 wt%.
Citation Information
Patent Citations
An electrochemical sensing fabric and its preparation method
CN109239152B
Surface amino-modified electrostatic spinning fiber-based friction nanometer power generator and preparation thereof
CN107493029A
Micro-order friction layer of nano power generator and preparation method of micro-order friction layer
CN110067082A
Elastic friction nano power generating yarn and preparation method thereof
CN111519300A
Gradient elastic polyurethane as well as preparation method and application thereof
CN114872416A